Gender-Specific Determinants of High Cholesterol: A Cross-Sectional Study Among Health Institution Employees in Makassar, Indonesia - Rudy Hartono; Rusli Rusli; Siti Nurul Fajriah; Mira Andini; Aswita Amir; M Askar (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
High cholesterol or dyslipidemia is one of the main risk factors for cardiovascular disease (CVD), including coronary heart disease, stroke, and peripheral artery disease. The World Health Organization (WHO) estimates that more than 39% of adults worldwide have total cholesterol levels above safe limits, with more than 4.4 million deaths each year directly related to increased LDL cholesterol levels and decreased HDL. Global trends show a significant increase in the prevalence of dyslipidemia in low- and middle-income countries, particularly in Southeast Asia, driven by changes in diet, urbanization, and decreased physical activity. At the national level, Basic Health Research (Riskesdas) and the Indonesian Nutrition Status Study (SSGI) report show that the prevalence of high cholesterol in Indonesia has continued to increase over the past decade. This study analyzed factors affecting high cholesterol using logistic regression in groups of women and men. The variables tested included blood pressure, body weight, and fasting blood sugar. Using data from 276 employees of a public health polytechnic in Makassar (January–June 2025), separate logistic regression models for women and men revealed that blood pressure was a significant predictor in both groups (ORwomen = 6.48, ORmen = 7.04), while fasting blood sugar was significant only in women (OR = 5.26). The results show that blood pressure is a significant predictor in both groups, while fasting blood sugar is significant only in women. The model explained 50.7% of variance in women versus 39.0% in men. The prediction model shows higher accuracy in women. These findings have important implications for gender-based dyslipidemia prevention efforts.